Classification of Fuzzy Logic Linguistic Terms for Accurate Load Balancing in Electric Power Distribution System. - Atim, Michael Robson; Anguma, Simon Katrini; Nabende, Jimmy Wanzala (International Conference on Electrical, Computer and Energy Technologies (ICECET), 2021)
Intelligent controls in electric power distribution system can be used to improve electric power distribution by balancing loads in a three-phase system at any time. One of such intelligent controls is fuzzy logic. In this paper we propose the use of unlimited linguistic terms for intelligent distribution management using fuzzy logic technique to rellocate phase load for a balanced three phase system in electric power distribution network system. The classified numerous linguistic terms culminate into numerous clustered regions of input load and output load change variables. These variables are used in fuzzy inference rules to provide the criteria for effective load balancing in three phases. The algorithm developed using the fuzzy set rules using seventeen clustered regions was subjected to the management of 2100 kW peak load in all the three phases. The simulation results showed balanced phase load with a peak load value close or equal to 700 kW per phase as expected. The developed fuzzy set rules is flexible and can be subjected to any grid load of interest to generate its algorithm. Furthermore, the simulation results of the developed fuzzy set rules and the subsequent generated fuzzy algorithm were subjected to the same test . The fuzzy logic algorithm developed in the current study gave low final values of maximum phase difference between two phases and subsequently low values of final absolute average unbalanced per phase.
Keywords: Fuzzy Logic; Load Balancing